IDENTIFIKASI FAKTOR DETERMINAN KETAHANAN KELUARGA MUSLIM PADA PASANGAN DIFABEL DI SUKOHARJO - Fadillah, Galih Fajar; Kholilurrohman, Kholil; Triyono, Triyono (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
Family is the smallest part of society but has a big role in forming a dynamic and developing society in accordance with the times. In a family, there are at least a father, mother and child who are often called the nuclear family. Each family member plays a role in maintaining the integrity of the family, especially the father and mother. This study aims to identify the determinants of family resilience in disabled couples. This study uses a case study method with data analysis techniques including pattern matching, explanation making and time series analysis. The subjects of this study were three disabled couples who had been married for more than 10 years and had children. Data collection instruments used interviews, observations and documentation. The main factors that support family resilience in disabled couples include marital commitment, social support, and religion. Research has shown that the third factor needs to be recognized by disabled couples in particular and the wider community in general, because family resilience in disabled couples is a joint struggle for the couple's extended family. Family resilience can be achieved through managing stress related to disability through effective communication, collaborative problem solving, and access to external resources. However, it is important to remember that resilience is not inherent or static; it is the result of a continuous process of adaptation and learning. Therefore, interventions that support families with disabilities should focus on strengthening social support systems, increasing accessibility, and providing adequate resources.